Study On The Indicators Village Aware (Concerned) Hiv-Aids In Indonesia - Febriansyah, Ferry (JOURNAL OF ECONOMIC SCIENCE, 2015)
Introduction: HIV-AIDS cases has been showed an increasing rate in Indonesia. Preventing and reducingÂ  risk of HIV transmission as well as reducing the social and economic impact of HIV-AIDS,Â  one of the strategies is to create an empowered people, therefore civil society can contribute significantly. To portray a society that has the power in preventing and controlling HIV-AIDS, can be seen from the level of awareness/community involvement which is demonstrated in addressing various issues related to HIV-AIDS. The level of awareness is reflected in the various components, which is subsequently identified to be an indicator of public concern.Methods: Used methods in this analysis are literature review and qualitative study. Data collection technique using indepth interview, focus grup discussion and observation. Qualitative study conducted in 22 group Concerned Citizens AIDS spread in 11 districts / cities in Indonesia with a total of 110 informants.Results: The results of qualitative studiesis coupled with the results ofthe literature review, concluded that the village aware (concerned) for HIV-AIDS have components: (1) Human Resources/Mobilization; (2) Forum; (3) Rules/Legality; (4) Media (Information, Education and Communication); (5) Funds; (6) Activity; and (7) Elimination of Stigma and Discrimination.Discusion: The study was carried out until the stage of determination of indicators, therefore it is necessary to test the application of these indicators in society.